Strategi Pemerintah Daerah Dalam Meningkatkan Daya Tarik Wisata Sejarah Dan Budaya Di Kabupaten Lingga Tahun 2022 - Ibnu Rizkan; Kustiawan Kustiawan; Ardi Putra (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
Historical and cultural tourism directly provides fulfillment in the form that tourism is a place of recreation, learning and knowledge and becomes a symbol of the area. Of course, in every area that has its own tourist selling power, including historical and cultural tourism in Lingga Regency, it will attract tourists, both local and foreign tourists, to come. still limited facilities and infrastructure supporting tourists both public facilities and tourist facilities are still limited in terms of quantity and quality such as lodging, transportation and tourism information services, government coordination both with the government and the private sector. seen from the strengths, weaknesses, opportunities and threats faced by the Lingga District Tourism Office. This study used a qualitative descriptive method with 5 (five) research informants consisting of the Head of Tourism Promotion and Marketing, Lingga District Head, Tourism Awareness Group (Pokdarwis), and the public or visitors. In this study the techniques used are in the form of observation, interviews, and documentation. In this study using the theory of SWOT analysis. The results of the study show that: a) the strength of the Local Government of Lingga Regency is supported by historical and cultural tourism objects which are managed directly by the Lingga Regency Tourism Office. b) Weaknesses of the Lingga Regency Tourism Office can be seen from the not yet optimal supporting facilities and infrastructure, namely limited transportation, access to remote areas, and supporting facilities at tourist sites. c) Opportunities for the Tourism Office to collaborate with tour travel, and focus on development in several historical and cultural tourism sectors, namely the Mepar Tourism Village, the Damnah Palace Site, the tombs and the Sultan's Mosque. d) The threat from the Lingga Regency Tourism Office is the lack of interest of the local community to visit historical and cultural tourism destinations in Lingga Regency.